2022
DOI: 10.1002/jccs.202200270
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals of mustard (Brassica Campestris) leaves tuned the nickel‐cobalt bimetallic oxide properties for enzyme‐free sensing of glucose

Abstract: The fabrication of enzyme‐free glucose sensors is highly demanded for the biological, clinical, and food applications. In this study, we have developed a green method for tuning the surface properties of nickel‐cobalt bimetallic oxide (NiCo2O4) by adding mustard (Brassica Campestris) leaves extract during hydrothermal growth. The mustard (Brassica Campestris) leaves extract is rich with a variety of phytochemicals, which can easily tune the surface properties of NiCo2O4 nanostructures, thereby paving the way t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Using XPS analysis, we were able to determine the chemical states and surface species of NiCo2O4 nanostructures both in the absence and presence of radish white peel extract, as shown in Figure 4. The XPS study has demonstrated a significant The presence of green organic recuing, capping, and stabilizing agents in the radish white peel extract have the capability to tailor the surface properties of nanostructured materials [28,42]. Using XPS analysis, we were able to determine the chemical states and surface species of NiCo 2 O 4 nanostructures both in the absence and presence of radish white peel extract, as shown in Figure 4.…”
Section: Structural and Morphological Investigations Of Radish White ...mentioning
confidence: 99%
“…Using XPS analysis, we were able to determine the chemical states and surface species of NiCo2O4 nanostructures both in the absence and presence of radish white peel extract, as shown in Figure 4. The XPS study has demonstrated a significant The presence of green organic recuing, capping, and stabilizing agents in the radish white peel extract have the capability to tailor the surface properties of nanostructured materials [28,42]. Using XPS analysis, we were able to determine the chemical states and surface species of NiCo 2 O 4 nanostructures both in the absence and presence of radish white peel extract, as shown in Figure 4.…”
Section: Structural and Morphological Investigations Of Radish White ...mentioning
confidence: 99%
“…The use of new synthetic methodologies has been demonstrated to be effective in increasing the performance of NiCo 2 O 4 nanostructures. 40,41 The use of biomass for tuning the catalytic activity of NiCo 2 O 4 nanostructured materials is considered extensively these days, hence different biomasses have been used during the synthesis. 40,41 Previous studies have used different biomasses containing phytochemicals and they have modied the surface properties of NiCo 2 O 4 nanostructures very effectively.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 The use of biomass for tuning the catalytic activity of NiCo 2 O 4 nanostructured materials is considered extensively these days, hence different biomasses have been used during the synthesis. 40,41 Previous studies have used different biomasses containing phytochemicals and they have modied the surface properties of NiCo 2 O 4 nanostructures very effectively. 40 Previously, the utilization of ascorbic acid and citric acid from citrus lemon juice has been explored in the synthesis of a ZnO material and its phase transformation, morphology and optical properties were studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wet chemical methods have gained significant attention in recent years due to their fast, facile, and promising characteristics. These methods are able to control the dimensions and shape of nanostructured materials by controlling the reaction conditions, such as pH, temperature, precursor concentration, and solvent volume [ 24 , 25 , 26 , 27 , 28 ]. Previous studies have employed hydrothermal methods to investigate the role of urea concentration on NiCo 2 O 4 nanostructures for electrochemical supercapacitor applications [ 25 ].…”
Section: Introductionmentioning
confidence: 99%